The Aestheticof Balance And Its Relationship To The Design of The Industrial Product Shape (Al-Academy, 2023)
The study tagged: (The aesthetics of balance and its relationship to the design of the body of the industrial product) discussed the role of balance in the design of industrial products of different shapes, colors and sizes, as well as their function. Based on the research problem that was determined by the following question: What is the relationship between balance and the design of the body of the industrial product? The aim of the research is to: reveal the statement of the effectiveness of the balance in the design of the industrial product body.The study was defined in four chapters: in the first chapter, a problem, the importance, and the aim of the research were presented. The second chapter contained the theoretical framework, as it included two sections, the first topic: the balance in the design of the industrial product body, and the second topic: the function and its balanced performance in the industrial product.As for the third chapter: it included the research procedures, from the methodology, a community, a sample, and the research tool, and in the fourth chapter, a set of results and conclusions were reached, and thus the recommendations.